A Review of Rural Communities’ Vulnerability to Climate Change: The Case of Limpopo Province in South Africa - RANKOANA, Sejabaledi (International Journal of Environmental, Sustainability, and Social Science, 2023)
Climate change threatens the livelihood of rural communities that depend on climate-sensitive resources. The risks and consequences of climate change, to which rural areas are especially susceptible, are discussed in this review. The review summarizes previous studies on rural communities' susceptibility to the impacts of changing climatic conditions. Previous studies on climate change in South Africa's Limpopo Province provide the information used in this review. The findings indicate that rural communities are vulnerable to rising temperatures and unpredictable precipitation. The communities are exposed to higher temperatures, less rainfall, and intermittent drought. Subsistence agricultural and livestock production and water supplies are two examples of climate-dependent livelihood resources vulnerable to weather variability and change. These resulted in food insecurity and water scarcity in many rural areas. This review helps fill a gap in understanding the importance of assessing the vulnerability of rural communities with climate-dependent livelihood resources. The study recommends detailed community-based adaptation measures to counteract the detrimental effects of climatic stresses on people's means of subsistence. Adaptation policies to climate change could be strengthened by incorporating indigenous adaptation techniques and community voices into response efforts.